THE CURRENT SITUATION OF CARE AND REHABILITATION NEEDS FOR DYSPHAGIA AMONG PATIENTS WITH ACUTE STROKE AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of dysphagia among patients with acute stroke at Vinmec Times City International General Hospital in 2025.Methods: Cross-sectional study.Results: The prevalence of swallowing disorders in stroke patients at Vinmec Times City International General Hospital in 2025 was as follows: severe swallowing disorders accounted for 51.7%, moderate swallowing disorders for 15.8%, and mild swallowing disorders for 2.5%. The majority of patients required complete assistance in daily living activities (76.2-77.4%); in communication (57.1%); and in basic motor activities (81%).Conclusion: The prevalence of dysphagia among stroke patients at Vinmec Times City International General Hospital, in 2025 was notably high. In addition, language and communication disorders were observed in a considerable proportion of patients, significantly impacting their quality of life.
Keywords: Dysphagia, stroke, GUSS scale.